Legal Protection for Land Rights Holders in the Event of Overlapping Certificates: Perlindungan Hukum Bagi Pemegang Hak Atas Tanah Jika Terjadi Tumpang Tindih Sertifikat - Yulianti, Melani (Annual Review of Legal Studies, 2024)
The effectiveness of the law in preventing and resolving cases of overlapping ownership of land certificates in Cirebon Regency is still not optimal. This can be seen from the continued issuance of SKT for land that has been certified, the lack of coordination between relevant agencies, the inadequacy of supporting facilities and infrastructure, and the low level of public legal awareness. Factors such as weaknesses in implementing regulations, weak law enforcement, limited information technology, and cultural aspects of society also contribute to this problem. To increase the effectiveness of land law, a comprehensive approach is needed that considers the interaction between law and non-legal factors, including the social, economic and cultural conditions of local communities. Legal protection for land rights holders (buyers) whose land overlaps with other certificates in the seller's name is not yet fully optimal. This is reflected in the lack of information transparency, minimal efforts to resolve disputes peacefully, as well as violations of buyers' rights by sellers. In this case of overlapping land certificates, the buyer in good faith suffers a loss because the certificate he has after the sale and purchase transaction turns out to be invalid and does not have a land object that matches the location indicated by the seller. This shows that there is legal uncertainty and a weak process for checking the validity of certificates by Land Deed Making Officials (PPAT) before buying and selling transactions. Even though the buyer's certificate must be destroyed due to legal defects, the buyer has the right to obtain legal protection from the Land Office in the form of issuing a new certificate, facilitating mediation or compensation, guaranteeing legal certainty, and law enforcement against parties involved in issuing fake certificates. This process must be carried out transparently and in accordance with regulations to ensure legal certainty for all parties.